THE POTENTIALS AND POSSIBILITIES FOR DEVELOPMENT OF TOURISTIC OFFER IN EASTERN MACEDONIA - Bizoev, Nikola (Journal of process management and new technologies, 2016)
The research of the touristic offer market indicates that the previous touristic arrangements that included a touristic offer of seven or fourteen days is not an attractive offer nowadays. We shall take into consideration the fact that current tourists prefer short vacations. As short trips are more required rather than long trips, the Eastern part of Macedonia has the potential and possibility for success in developing the touristic offer. Trends of short trips shall be the turning basic point when creating the touristic offer in this part of Macedonia. The private accommodation in the Eastern part of Macedonia is closely related to the rural way of living, which is a great advantage comparing to enormous hotels, as tourists expect to experience a difference. For this purpose, tourists must be offered with activities with which certain destinations would be sold as a unique touristic product with precised and interesting story, authentic offer and high quality accommodation infrastructure. This kind of sell requires numerous activities and contracts between local communities, agencies and local entrepreneurship. It is necessary the destination management to be on a high functional level as previous experiences include excellent results.